A municipal solid waste indicator for environmental impact: Assessment and identification of best management practices - Deus, Rafael Mattos [UNESP]; Mele, Fernando Daniel; Bezerra, Barbara Stolte [UNESP]; Battistelle, Rosane Aparecida Gomes [UNESP] (Elsevier, 2020)
The objective of this study was to develop an aggregate indicator to assess the environmental impact of municipal solid waste management in the small municipalities of the state of São Paulo, Brazil. Additionally, the study aimed at creating a classification of the municipalities considered to identify the best management practices. The study consisted of five phases: Phase 1: Selection of municipalities; Phase 2: Data collection (inputs); Phase 3: Use of the Waste Reduction Model; Phase 4: Analysis of results (outputs) and; Phase 5: Construction of the aggregate indicator and comparison between municipalities to analyze management practices. The results showed that the average waste generation was 223.89 kg (inhabitant−1 year−1), the average carbon dioxide equivalent (CO2e) emissions was 0.166 tons (inhabitant−1 year−1), the average amount of energy savings was 51.37 kWh (inhabitant−1 year−1) and that most municipalities had suitable final waste destinations. After developing the aggregate indicator, which was a geometric mean of the normalized indicators for waste generation, emissions of CO2e, energy consumption and quality of final destination, the municipalities were ranked. Among the ten best-ranked municipalities, six of them disposed of the waste in municipal landfills, and four, in private landfills. Only one municipality is part of a consortium, while seven of them have institutionalized selective collection. One of the critical points for good indicators is the presence of waste pickers. For further improvements in the management of these municipalities, it is suggested that practices involving recycling and the integration of waste pickers with proper technical training are developed and implemented further. It is also recommended fostering greater social inclusion and integrated participation in the management of municipal solid waste. The aggregate indicator developed was regarded as appropriate to assess the environmental impact of municipalities and to classify them, allowing the identification of the best management practices.
Keywords: Carbon dioxide equivalent; Environmental analysis; Indicators; Strategic waste management